The Kingdom of Saudi Arabia: Achieving the Aspirations of the National Transformation Program 2020 and Saudi Vision 2030 Through Education (Journal of Education and Development, 2018)
The research described and reported on in this article focuses on an analysis of the Saudi Arabian National Transformation Program 2020 and Saudi Vision 2030. The investigation involved a document analysis of these documents in order to identify the associated curriculum orientations within these documents to determine what the Kingdom of Saudi Arabia is seeking to achieve and how it envisages achieving these aspirations through education development. The analysis revealed that the goals and aspirations of the Kingdom have increasingly become more clearly defined with attention to alignment between national education goals and economic development whilst ensuring that practices are consistent with Islamic beliefs. In brief, as evidenced in the documents, the analysis reveals that the imperative of the National Transformation Program 2020 and Saudi Vision 2030 is to establish a ‘Saudized’ knowledge-based economy; and education is seen to be a means by which this imperative is to be fostered.